1, 3‐Dipolar Cycloaddition Reactions of Indan‐1‐one Enamines across Arylnitrile Oxides Leading to Novel Cyclic Isoxazoline Derivatives. (18th November 2013) - Jelizi, Hanene; Wannassi, Nadia; El Baker Rammah, Mohamed; Ciamala, Kabula; Knorr, Michael; Rousselin, Yoann; Kubicki, Marek M.; Strohmann, Carsten; Enescu, Mironel
<x xml:space="preserve">Abstract</x> Synthesis of a series of cyclic fused‐isoxazolines has been accomplished by regioselective and diastereoselective1, 3‐dipolar cycloaddition of 3‐methylindan‐1‐one enamines (1a, 1b, 1c) and 3‐phenylindan‐1‐one enamines (2a, 2b, 2c) to arylnitrile oxides (3d, 3e, 3f, 3g, 3h). The structure of the cycloadducts was elucidated by 1H and 13C NMR spectroscopy. The proposed regio‐ and stereochemistry of fused‐compounds (4) and (5) has also been corroborated by two single‐crystal X‐ray diffraction studies carried out on 4‐methyl‐8b‐morpholinyl‐3‐(p‐tolyl)‐4H‐3a, 8b‐dihydroindeno[2, 3‐d]isoxazoline (4be) and 3‐(p‐anisyl)‐4‐phenyl‐8b‐pyrrolidinyl‐4H‐3a, 8b‐dihydroindeno[2, 3‐d]isoxazoline (5af) and by means of density functional theory calculations.